Real‐time PCR for quantification in soil of glycoside hydrolase family 6 cellulase genes. (1st September 2014) - Merlin, C.; Besaury, L.; Niepceron, M.; Mchergui, C.; Riah, W.; Bureau, F.; Gattin, I.; Bodilis, J.
Abstract: Cellulose is the main structural component of the cell walls of higher plants, representing c . 35–50% of a plant's dry weight; after decomposition and transformation, and constituting a large part of soil organic matter. Telluric micro‐organisms able to use cellulose as carbon and energy sources for growth are widely distributed in the environment, but the factors controlling the rate of cellulose degradation are not well understood. In this study, we have developed a quantitative real‐time PCR (qPCR) primer set to quantify the glycoside hydrolase family 6 (GH6 family) cellulase genes in soil samples. The qPCR assays were linear over 8 orders of magnitude and sensitive down to 10 copies per assay. qPCR analysis of contrasted soil samples showed densities between 2·47 × 10 7 and 1·48 × 10 10 copies per gram of soil. Cloning and sequencing of the PCR products from environmental DNA confirmed both specific amplification (more than 96%) and the wide diversity targeted by the primer set, throughout nearly all the GH6 family, including sequences of bacteria and fungi. Significance and Impact of the Study: Telluric micro‐organisms able to use cellulose as carbon and energy sources for growth are widely distributed in the environment, but the factors controlling the rate of cellulose degradation are not well understood. The objective of our study was to develop a qPCR for rapid quantification of GH6 cellulase genes in soil. This qPCR could be applied to study the potential for cellulose degradation in different soils in order to better understand the factors controlling the stability of the soil organic matter.